Effects of 071031B, a novel serotonin and norepinephrine reuptake inhibitor, on monoamine system in mice and rats - Rui Xue; Xin-Hua He; Li Yuan; Hong-Xia Chen; Li-Ming Zhang; Zheng Yong; Gang Yu; Shi-Yong Fan; Yun-Feng Li; Bo-Hua Zhong; You-Zhi Zhang (Elsevier, 2016)
Our previous study indicated that 071031B, a novel potential serotonin and norepinephrine reuptake inhibitor, showed robust antidepressant activity in multiple depression models, and could simultaneously inhibit 5-HT and NE reuptake in vitro. The present study was to evaluate the effects of 071031B on monoamine system in vivo, by using pharmacological models, including 5-HTP induced head-twitch test, yohimbine toxicity potentiation test, and reserpine induced hypothermia test, and determining monoamine transmitter levels in reserpine induced monoamine depletion model or chronic unpredictable stress (CUS) model. Results in pharmacological models indicated that acute administration of 071031B at 5-20 mg/kg significantly enhanced 5-HTP induced head-twitch behavior, potentiated yohimbine induced lethal rate, and reversed reserpine induced hypothermia. Further monoamine assays demonstrated that acute or chronic administration of 071031B at 10 or 20 mg/kg increased 5-HT and/or NE levels in various brain regions in reserpine or CUS induced monoamine depletion models, respectively, without effect on DA and its metabolites. Our results revealed that 071031B produces potent inhibition of 5-HT and NE reuptake in vivo.